La integración de las mujeres inmigrantes cualificadas en Dinamarca: Estrategias y la Red de Mentoras KVINFO - Juárez Peña, Marta Leonor (Servicio de Publicaciones y Divulgación Científica, 2016)
The research aim of this thesis is to analyse the integration process of skilled immigrant women in Denmark. Special attention is paid to the labour integration dimension as an important part of the global process of social integration. The perspectives are those of the host society and of the originating societies of the immigrant population being studied. Gender perspective is also analysed. The unit of analysis is the immigrant women, of different origins and ages, and that has in common their high school education. It is assume that the Danish state has to resolve other immigration-related issues considered to be of greater importance: the problems related to the low-skilled immigrant population, which is difficult to integrate. The research is undertaken in the social context of the 2001 to 2008. The fieldwork focuses on Copenhagen and the Capital area. THEORETICAL BACKGROUND The objectives are ascertaining the extent of integration of skilled immigrant women in Denmark, knowing the obstacles immigrants high skilled women face in the process of entering the Danish labour market, determining the strategies they develop for the sake of achieving integration. Knowing where the immigrant society and Danish society meet, knowing the role of private and public organisations (such as the Kvinfo network of mentors that connects professional immigrant women with professional Danish women who act as mentors of the former in the labour market) in the social integration process of the skilled female immigrant population in Denmark. The hypotheses are, on the one hand, that there is a tendency among highly skilled immigrant women to try to recover their occupational status. This decision tends to hold a very secondary place in the integration process of the family unit, to the extent that it can be completely overshadowed as a result of the passage of time. The second hypothesis is that the increase of immigrant groups in Denmark will provoke a revision of the current concept of the "welfare state" due, among other reasons, to the role played by civil society via the volunteer figure of professional women. The third hypothesis, is that immigrants who are less skilled and more dependent on the Danish welfare system appear to be more likely to remain in the host country. One of the main objectives of this research is to extol the role of high-skilled immigrant women with the goal of recovering their professional status lost or undermined in the migration process. The final integration process of immigrants is understood as the result of the encounter between the aspirations and strategies of immigrants, and the characteristics and conditions occurring in the host country. The economic dimension determines the immigrant integration process in the host society, but there is also interdependence with the cultural and social dimensions. The integration strategies developed by highly skilled immigrant women depend on the immigrant's available resources; the rights and duties of the host countries; and immigration social networks. METHODOLOGY The methodology applied consists on a qualitative and quantitative analysis. There have been used both primary and secondary data to meet the objectives of this research. The primary data has come from open individual interviews; the secondary data comes from a series of document sources and specialised official statistics, including the 2013, 2012, and 2006 Reports on Data and Figures on Immigration Matters, and the Data Report on Integration, Welfare and Development, from December 2012. The Kvinfo Mentor Network has been used for the interviews, as allows access to immigrants who had spent a short period of time in Denmark. Later on the snowball sampling technique was used. CONCLUSIONS The Danish integration policies have been designed in a completely one-way manner. They are measures designed for immigrants, but without involving the efforts of the labour market Danish system representatives. Among the Danish values most admired by immigrants, it is equality of opportunities among citizens, equality of gender-related conditions and, as a result of all this, the security that this entails. However, there is also a side of the Danes that is somewhat criticised by immigrants: the certain coldness character, superficiality, and materialism when socialising. As a result, there is total unanimity among immigrants when asserting that they did not feel socially integrated in Denmark. This is also the reason they defend the need to participate in associations or organisations where it is easier to meet or relate to the Danes. The best strategy to solve the reservations of the Danes towards immigrants has the following ingredients: respect towards Danish norms and values; learning the language; and finding employment. The most important conclusion deduced from this research is that all women interviewed have an essential objective: to recover their professional lives or professional identities, accepting the need to adapt to the new demands of the labour market of Denmark. Additionally, given the natural tendency of Danish people towards associationism, immigrants quickly learn that the best way to make contacts is through organisations or associations. BIBLIOGRAPHY Boswell, Ch. (2003): European Migration Policies in Flux. Changing Patterns of Inclusion and Exclusion. The Royal Institute of International Affairs, Blackwell. Castles, S. (2002): “Migration and Community Formation under Conditions of Globalization”. International Migration Review, Vol. 36, págs. 1143 – 1168 Freeman, G.P. (2004): “La incorporación de inmigrantes en las democracias occidentales”, International Migration Review, monográfico dedicado al diálogo transatlántico, 38 (3), p. 945 – 969. Jiménez Juliá, E. (1998): “Una Revisión Crítica de las Teorías Migratorias desde la perspectiva de género”, Revista Estudios Migratorios del Consello da Cultura Galega. Centre d ́Estudis Demogràfics. Liebig, Th. (2007): The Labour Market Integration of Immigrants in Denmark, OECD Social, Employment and Migration Working Papers, DELSA/ELSA/WD/(2007) 5. Liversage, A. (2009): “Vital conjunctures, shifting horizons: high-skilled female immigrants looking for work”; SFI The Danish National Centre for Social Research. Portes, A. (1979): “Illegal Immigration and the International System: Lessons from Recet Legal Mexican Immigrants to the United States”, American Sociological Review No 34; pp: 505-518. Sassen, S. (1994): Cities in a World Economy. Pine Forge Press (Thousand Oaks, Calif.). Tapia Ladino, M. (2011): “Género y Migración: Trayectorias investigativas en América Latina”, Revista Encrucijada Americana; Pp: 115-147.
Keywords: Inmigrantes; Inmigrante; Cualificación; Alta; Tesis Doctoral; Dinamarca; Integración; Social; Laboral